Adaptability and stability of maize cultivars in Brazilian Northeast - Carvalho, Hélio Wilson Lemos de; Cardoso, Mílton José; Leal, Maria de Lourdes da Silva; Santos, Manoel Xavier dos; Tabosa, José Nildo; Souza, Evanildes Menezes de (Pesquisa Agropecuaria Brasileira, 2005)
Forty six maize cultivars were evaluated during two years in 11 different places of Brazilian Northeast Region. Trials were carried out during the biennium 2001/2002 using experimental randomized block design, three repetitions, in order to know the adaptability and stability for cultivars recommendation. It was verified that the cultivars showed differentiated behavior among themselves in the mean of environments. The magnitude of the variance for local x cultivars interaction was more expressive than cultivars x years interaction, which suggests that the evaluations have to be done in a larger number of environments. Evaluated cultivars differed in adaptability and stability, and are very important for Brazilian Northeast Region.